Adubação de sistemas: volatilização de amônia em área de integração lavoura-pecuária em experimento de longa duração - Lima, Rosangela Corrêa de (2018)
The crop-livestock integration, besides intensifying the use of land, adding income to the rural producer, brings many other benefits to the agricultural systems. One of them is the greater efficiency in the use of nitrogen fertilizers, caused by the greater cycling and recycling of nutrients between the pasture phase and the cropping phase, which reduces production costs and makes the system more sustainable in the long term, due to the lower rate of losses of N. In this context, the objective of this work was to evaluate the losses by volatilization of ammonia due to the application of N and the height of pasture management in the area of crop-livestock integration. The experiment was carried out in an area of 14 ha, where since 2012 a long-term experiment has been conducted with ILP under Plantio Direto. Four rotating crops were evaluated during two agricultural crops: ryegrass (2016/2017), and oat-corn (2017/2018). The experimental design for the winter crop was in randomized blocks in a factorial scheme (2x2x7), with three replications. The first factor was nitrogen (N) application time in the system: N applied to the pasture (N-Pasture) and these were the only plots to receive coverage N at the dose 200 kg of N ha-1 in a single application at this stage which were compared with the plots denominated N- Fertilization Grains, which did not receive nitrogen fertilization in the grazing phase. The second factor was grass height, High Height (AA) and Low Height (BA), 25 and 10 cm (intended heights), respectively. As a third factor, the days of collection were evaluated after the application of N, which were performed at 2°, 4°, 6°, 8°, 10°, 12° and 14° day after the application of urea. For the grain culture, another factor (2x2x7x4) was added, with increasing doses of N: 0; 50; 100 and 150 kg ha-1, and 0; 100; 200 and 300 kg ha-1, for the bean and corn crop, respectively. They were allocated in subplots within each plot, at the time of application of the N in cover in the treatment N-Fertilization Grains. The evaluation of ammonia volatilization was performed by the method of static semi-open collectors and the quantification of the ammonia content was performed by the colorimetry method. Ammonia volatilization losses for both winter and summer crops were influenced by the treatments in which they were submitted and were highly dependent on the climatic conditions at the time of N application. The accumulated losses caused by ammonia volatilization by nitrogen fertilization (urea) were minimal, being lower than 1.5% in the two years of evaluation in the grazing phase. In the bean and corn cultivation phase the maximum accumulated ammonia volatilization loss observed was 5.37% and 4.0%, respectively. Higher grazing pressure resulted in lower losses due to ammonia volatilization during the grazing phase and, conversely, during the grazing phase a higher grazing pressure applied to previously cultivated grazing resulted in higher losses due to volatilization of ammonia.